2009
DOI: 10.3917/tgs.021.0131
|View full text |Cite
|
Sign up to set email alerts
|

Les femmes dans le processus d'expatriation

Abstract: Résumé Avec, d’une part, la mobilité internationale des cadres, exacerbée dans les entreprises par la croissance mondiale et, d’autre part, des compétences managériales, un niveau de formation et une participation à la vie active comparables pour les hommes et pour les femmes, tous les éléments semblent réunis pour assurer une représentation égale des deux sexes dans les rangs des expatriés. Paradoxalement, alors que la population active se féminise, celle des expatriés reste majoritairement masculine. Les fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Indeed, Caligiuri and Tung (1999), using a unidimensional measure of adjustment, found that female expatriates tend to report lower adjustment than men in countries with lower workforce participation of women. Mérignac (2009) extended these findings by showing that women's labor participation rate in the host country was significantly and strongly correlated with female expatriates' interaction adjustment. In Switzerland, as explained in Section 4.1, women's workforce participation rate is very high in international comparison, and is higher than in most of expatriates' home countries in the current study (e.g.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Indeed, Caligiuri and Tung (1999), using a unidimensional measure of adjustment, found that female expatriates tend to report lower adjustment than men in countries with lower workforce participation of women. Mérignac (2009) extended these findings by showing that women's labor participation rate in the host country was significantly and strongly correlated with female expatriates' interaction adjustment. In Switzerland, as explained in Section 4.1, women's workforce participation rate is very high in international comparison, and is higher than in most of expatriates' home countries in the current study (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…However, this might not necessarily lead to lower work adjustment for women. Indeed, although often exacerbated abroad, many of these barriers may not be new to female expatriates, since they may already have faced them in their home country and could thus be well prepared for dealing with them abroad (Mérignac, 2009). Going a step further, Janssens et al (2006) argue that, instead of being systematically presented as "powerlessly caught in a penalizing structural context" (p. 133), female expatriates should much more be viewed as active agents, able to produce empowering identities that purposively contribute to their success in the workplace.…”
Section: Female Vs Male Business Expatriatesmentioning
confidence: 99%
See 1 more Smart Citation
“…En raison des préjugés des hiérarchiques et/ou des directions des ressources humaines, les femmes cadres sont moins sollicitées ou retenues pour une expatriation en raison de leur moindre mobilité supposée ou de destinations considérées comme problématiques pour des raisons culturelles ou religieuses (Forster, 1999 ;Mérignac, Roger, 2006). Quand elles arrivent à contourner ces préjugés, souvent à leur propre initiative, elles envisagent souvent le célibat géographique au départ comme une solution temporaire adéquate, notamment les trentenaires sans enfant (Mérignac, 2009). Elle s'avère risquée au niveau privée si elle se pérennise, à la fois pour le couple mais aussi pour les projets de maternité (projets reportés puis abandonnés, sans véritable choix).…”
Section: Stratégies Familiales Et Résidentielles : Le Choix De L'instunclassified